-9x+5(-3x-4)=-42-2x

Simple and best practice solution for -9x+5(-3x-4)=-42-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x+5(-3x-4)=-42-2x equation:


Simplifying
-9x + 5(-3x + -4) = -42 + -2x

Reorder the terms:
-9x + 5(-4 + -3x) = -42 + -2x
-9x + (-4 * 5 + -3x * 5) = -42 + -2x
-9x + (-20 + -15x) = -42 + -2x

Reorder the terms:
-20 + -9x + -15x = -42 + -2x

Combine like terms: -9x + -15x = -24x
-20 + -24x = -42 + -2x

Solving
-20 + -24x = -42 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-20 + -24x + 2x = -42 + -2x + 2x

Combine like terms: -24x + 2x = -22x
-20 + -22x = -42 + -2x + 2x

Combine like terms: -2x + 2x = 0
-20 + -22x = -42 + 0
-20 + -22x = -42

Add '20' to each side of the equation.
-20 + 20 + -22x = -42 + 20

Combine like terms: -20 + 20 = 0
0 + -22x = -42 + 20
-22x = -42 + 20

Combine like terms: -42 + 20 = -22
-22x = -22

Divide each side by '-22'.
x = 1

Simplifying
x = 1

See similar equations:

| 40+40*0+1= | | 2x+7(3x-4)=-2-3x | | -8x^2+24x-18= | | -16+x=450 | | 5x^2+50x=0 | | -5x+x=-16 | | 120x^2-272x+120=0 | | 5*5*5*5= | | 2t^2+2t=3 | | 10-3(-8-2)= | | 120x^2-272x+102=0 | | 10x-0.375-4x=6x | | 2+x=16-6x | | 30a=2a-8 | | 976x-x^2=213.495 | | 1/14=27/7*1/30 | | 10x-2y=5 | | -2x^2+17x-8=0 | | 6x-2y=1 | | -99=33y | | 8j-4k=4 | | 5(k-2)-6=5k-(4k-3) | | 3j+4k=23.5 | | 11f+10g=25 | | Y=150x+800 | | 22=-2+3s | | -2-19= | | 4m(4n-8)+6mn-2m= | | -39(11x)+26(24x)= | | 3r-6t=15 | | 6r-6t=6 | | 4x=14-2x |

Equations solver categories